Marker-based Augmented Reality Application for Car Basic Maintenance (International Journal of Innovative Computing, 2023)
In general, Augmented Reality (AR) is a technology that allows the virtual object to complement the real-world environment. The rapid growth of technology has enabled mostly anyone to use AR technology. Thus, applying AR technology in the learning experience should normalize as it is now easy to access and there is much positive feedback based on the past research regarding AR in education. Unlike watching tutorial videos, AR teaching applications would provide users with different learning experiences. Therefore, the aim of this research is to provide more immersive learning experiences to drivers to learn simple car maintenance. This application will illustrate 3D steps and procedures of simple car maintenance for drivers to learn in helping them to self-service their car. Consequently, there are 4 phases of this project that need to be carried out to achieve the objectives of this research. The first phase is to review the AR application concept and understand the car services techniques. The second phase is to design and develop the AR application that will provide simple car services techniques. The third phase is integrating the AR car services manual and finally evaluating the effectives of this application in providing the car basic maintenance tasks and knowledge to new drivers. The evaluation discovered that the drivers have more interaction during learning experience using the AR application.
Keywords: Augmented Reality, Handheld device, Car maintenance